(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
The current study aims to compare selected Gnostic conceptual categories from Nag Hammadi texts with the literary version of gnosis proposed by Bruno Schulz (1892–1942). He was not aware of the texts found in 1948, but he utilized his knowledge of Gnosis and Gnosticism, which was accessible in the Polish literary community at that time. This included his study of early Christian anti-Gnostic polemicists. The proposed comparison of text fragments from Nag-Hammadi with Schulz’s gnosis seeks to demonstrate the ongoing literary appeal of the apocryphal nature of Gnostic gnosis in the writing of the teacher of the drawings from Drohobych.